2005
DOI: 10.1038/sj.eye.6701931
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyaluronidase on ocular motility and eyelid function in sub-Tenon's anaesthesia: randomised controlled trial

Abstract: Purpose To assess the effect of hyaluronidase on eye and eyelid movements when used as an adjunct in sub-Tenon's anaesthesia. Methods A total of 60 patients who had subTenon's anaesthesia prior to phacoemulsification surgery were divided into two equal groups in a double-masked randomised controlled fashion. Of these, Group A had 4 ml lignocaine 2%, while Group B had 4 ml lignocaine 2% with the addition of sodium hyaluronidase 75 IU/ml. Ocular motility, levator, and orbicularis oculi function were measured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…Pain scores (visual analogue scale) were not significantly different between the groups. Aslam et al 22 found improved akinesia with 75 IU ml −1 but did not assess analgesia.…”
Section: Hyaluronidasementioning
confidence: 95%
“…Pain scores (visual analogue scale) were not significantly different between the groups. Aslam et al 22 found improved akinesia with 75 IU ml −1 but did not assess analgesia.…”
Section: Hyaluronidasementioning
confidence: 95%
“…This is comparable to the onset of action reported in this study which used bupivacaine. Mixtures of bupivacaine, lidocaine, and hyaluronidase are often used in human ophthalmology to minimize the time to onset . While this is very important for rapid case flow through busy human surgical theaters, the time to onset of action of STA is not a rate‐limiting step in canine cataract surgery.…”
Section: Discussionmentioning
confidence: 97%
“…Alwitry et al 16 reported that hyaluronidase (150 units) facilitates the onset of ocular anaesthesia, whereas Moharib et al 17 showed no difference in the time of onset of akinesia using 75 units of hyaluronidase. Aslam et al 11 demonstrated an improvement in ocular and lid akinesia with the addition of 75 units of hyaluronidase. Our study shows that a group of patients who received 300 units of hyaluronidase had better OASS scores compared with a group that received 150 units.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have measured akinesia alone 10 11. Alternatively, the efficacy of anaesthesia has been studied through patient satisfaction surveys that relied on qualitative statements by patients and surgeons12 or using tools such as the Visual Analogue Pain (VAP) scale7 13 and the Iowa Satisfaction with Anaesthesia Scale (ISAS) 14…”
mentioning
confidence: 99%